Effect of Azolla pinnata meal on growth, immunity, faecal E. coli, antioxidant capacity and gut histomorphology in Japanese quails - Abdul Hafeez; Darwish Khan; Shabana Naz; Rasha Alonaizan; Rasha K. Al-Akeel; Muhammad Israr; Rifat Ullah Khan (Journal of Applied Animal Research)
Amidst increasing concerns regarding the incorporation of non-traditional protein sources in poultry diets as replacements for protein sources vital for human consumption, such as soybean meal, the utilization of Azolla leaf meal has garnered significant attention and popularity. The experiment commenced with 192 Japanese quail chicks (one day old), originated from a single hatch. Each chick was individually weighed and then randomly assigned to one of four treatment groups, namely control, supplementation of Azolla at the rate of 20 g/kg (Azolla 20), 40 g/kg (Azolla 40), and 60 g/kg (Azolla 60). Weight gain, feed conversion ratio (FCR) and dressing percentage were significantly (P < 0.05) higher in Azolla 40 and Azolla 60 compared to the control. No significant (P > 0.05) difference was found in antibody titre against New Castle disease virus, maleanodialdehyde (MDA) and faecal E. coli excretion. Further, villus height, crypt depth and ratio between them improved significantly (P < 0.05) in Azolla 60 compared to the control. In conclusion, our findings demonstrated a favourable impact of incorporating Azolla meal into the Japanese quail diet, leading to improved growth rates attributed to its positive influence on intestinal morphology. However, no significant effects were observed on immune response, lipid peroxidation, or faecal E. coli levels.